A New Extended VIKOR Approach Using q-Rung Orthopair Fuzzy Sets for Sustainable Enterprise Risk Management Assessment in Manufacturing Small and Medium-Sized Enterprises - Cheng, Sun (2021)
In recent years, the important role of sustainable development is highlighted in the literature; therefore, a company to make a sustainable business success needs to be well focused on social, environmental, economic, and technological characteristics of the business to address risks and capture value properly. The process of Sustainability Enterprise Risk Management (SERM) is typically implemented to integrate all social, economic, environmental, and technological aspects in a systematic way to properly manage emerging risks and other non-quantifiable risks for company survival. Therefore, in this study, an attempt has been carried out to develop a comprehensive framework to implement the ERM framework under the sustainability platform by considering 29 sub-criteria based on four main aspects, including social, environmental, technological, and economic. In addition, a new fuzzy decision-making approach using the VIKOR (VlseKriterijumska Optimizacija Kompromisno Resenje) approach under q-rung orthopair fuzzy set (q-ROFSs) called VIKOR-q-ROFSs approach is introduced to identify, rank, and evaluate the main criteria of SERM in the universal appeal for all industries such as Chinese manufacturing Small And Mid-Size Enterprises (SMEs) based on expert opinions and literature review. To determine the weights of SERM criteria by the decision experts, this study has introduced q-ROFNs. Moreover, to facilitate the q-ROFNs, a novel q-rung orthopair fuzzy weighted averaging operator (q-ROFWAO) is proposed. Furthermore, VIKOR is applied to rank and evaluate the manufacturing SMEs as the alternatives for this study. The results of this paper showed that technological suitability was the important risk factor followed by technological advance, occupational safety and health, product and services responsibility, (benefit) anti-corruption labor practices, and technological practicability. In addition, the findings of the analysis show that the proposed method was efficient and effective in evaluating risk assessment of SERM in the SMEs